Position paper on postgraduate medical education on the occasion of hospital reform – postgraduate medical education must be considered. A joint position paper by Bündnis Junge Ärztinnen und Ärzte and AG Junge Gastroenterologie of the DGVS as well as the Young DGN. Positionspapier zur ärztlichen Weiterbildung anlässlichder Krankenhausreform – die Weiterbildung mussmitgedacht werden. Ein gemeinsames Positionspapierdes Bündnis Junge Ärztinnen und Ärzte und der AG Junge Gastroenterologie der DGVS sowie der Young DGN - Hahn, Eckhart (GMS Journal for Medical Education, 2024)
The Bündnis Junger Ärztinnen und Ärzte (BJÄ, Alliance of Young Physicians in Germany) has presented a position paper (PP) on Postgraduate Medical Education (PGME) against the background of an unfolding hospital reform in Germany, and they describe existing deficits of PGME in Germany. Based on this, demands were made of legislators, employers and medical associations which could result in a sweeping reformation of PGME. Hospital reforms can only be accomplished with well trained and motivated physicians. In this respect the BJÄ regards the reform of hospitals and the health-care system as a chance for a reform of PGME, which is long overdue. Legislative competence for PGME lies with the States of the Federal Republic of Germany and this warrants an adjustment of state medical association laws to accommodate the demands of the BJÄ. Generally PGME must be taken into consideration in all health-care legislation, in analogy to the meanwhile globally adopted principle of “Health in all Politics (HiAP)”. The BJÄ has made every endeavour to produce this PP. The responsible stakeholders and actors in the health-care system would be well-advised to take the position paper seriously with a dwindling physician work force in hospitals and serious quality deficits in PGME. Hence, the BJÄ must be comprehensively supported. They need congenial partners to define the scientific foundation of all their demands, to test their application under real life conditions in hospital and outpatient care, to pursue research on the impact on patient care and on the intended transformation of the healthcare system. This might best be accomplished by partnering with a scientific Association for Postgraduate Medical Education as has been the case in many countries for decades.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Alliance of Young Physicians in Germany); Bündnis Junge Ärztinnen und Ärzte (BJÄ; German Association for Postgraduate Medical Education; hospital reform in Germany; hospital transparency law in Germany; position paper postgraduate medical education; postgraduate medical education on Germany